The Romans : An Introduction - Graham, Abigail (Peoples of the Ancient World Ser, 2020)
Cover -- Endorsements -- Half Title -- Title Page -- Copyright Page -- Dedication -- Table of Contents -- List of figures -- List of maps -- Acknowledgments -- Advice on using ancient sources: Caveat Lector (Reader Beware)! -- Companion website -- General introductions and websites -- 1. THE ORIGINS OF ROME -- Foundation legends and their sources -- Rome: center of the universe -- Further reading -- 2. THE REPUBLIC (510-60 BC) -- The birth of the Roman constitution (509-281 BC) -- Origins of empire: Roman warfare and imperialism (281-121 BC) -- The twilight of the Roman Republic: administering an empire 121-60 BC -- Further reading -- 3. THE RISE OF THE ROMAN EMPIRE: TWELVE CAESARS (60 BC-AD 96) -- Sources on the Twelve Caesars -- The first triumvirate (60-48 BC) -- The rise of Augustus and the second triumvirate -- Augustus: restorer of the republic? -- Tiberius (AD 14-37) -- Caligula (AD 37-41) -- Claudius (AD 41-54) -- Nero (AD 54-69) -- The year of four emperors: summer 68-winter 69 AD -- Vespasian (AD 69-79) and the Flavian dynasty -- Titus (AD 79-81) -- Domitian (AD 81-96) -- Further reading -- 4. THE ROMAN EMPIRE: ZENITH AND DECLINE (AD 96-330) -- Making the Empire work -- Sources: Cassius Dio, Ammianus and the Historia Augusta -- The "five good emperors" (AD 96-180) -- The Severans: the disintegration of dynasty (AD 180-234) -- The 3rd-century crisis? Devaluation and disorder (AD 235-284) -- Recovery: Diocletian, Constantine and Christian Rome (AD 284-337) -- Further reading -- 5. ROMAN RELIGIONS AND MYTHOLOGY -- Roman divinities -- Prayer and sacrifice: blessings and curses -- Omens -- Worship in the home -- Worship in the fields -- State religion: offices -- State religion festivals and the calendar -- Religion in the provinces: east meets west -- Jews and Christians -- Further reading -- 6. SOCIETY AND DAILY LIFE -- Social hierarchy.